Correlation of Dentolabial and Facial Analyses with Aesthetic Perception - Onur Şahin; Ayşegül Köroğlu; Zeynep Aydin (Atatürk University, 2024)
Objective: : It may be necessary to systematically apply objective, measurable and repeatable rules for physicians to provide an aesthetic smile in patients and for evaluations. The aim of this study was to evaluate the consistency of the aesthetic perception of physicians with the results of objective dentolabial and facial analyses and the state of being affected by professional experience.Methods: In the current study 4 prosthodontists, 4 research assistants and 4 intern dentists were determined as observer and they were asked to evaluate the full face and smile photographs taken from 100 volunteers in the context of 6 criteria for aesthetics. The relevant photographs were analyzed objectively in digital environment, taking into account the values determined as reference with the support of the literature. Statistically, the comparisons between subjective results of the observers and the objective reference values were determined with Cohen's Kappa test; consistency between observers were with Fleiss Kappa statistic; the comparisons of facial and dentolabial esthetic perceptions were made by Chi-square test.Results: The results obtained by the subjective perceptions of all observers and the objective results of computer measurements were not completely compatible with each other statistically, but a great deal of agreement was achieved. The harmony of aesthetic perception with objective results was not affected by increasing professional experience and no difference was observed between the observer groups.Conclusion: Examining not only the mouth but also the whole face analysis results in aesthetic evaluations has the potential to positively affect the success of the treatment.